Plant Adaptation to Extreme Environments in Drylands (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Our reprint consists of 13 papers. In the first five papers, the influencing factors of biodiversity and community composition are addressed. In the sixth and seventh papers, the spatial distribution patterns and drivers of arid plants under the background of global climate change are examined. The eighth paper describes leaf stoichiometry in arid zones. The ninth studies the change in carbon allocation depending on plant growth stage and the tenth deals with the use of condensed water by plants. Papers 11-13 look at the relationship between plants and soil.